Taguchi optimization of a SiGe/Si quantum dot SOI-based lateral PIN photodiode - Menon P.S.; Tasirin S.K.; Ahmad I.; Abdullah S.F. (Trans Tech Publications, 2023)
A high performance lateral silicon photodiode was designed on a Silicon-on-insulator (SOI)-based substrate with SiGe/Si quantum dot technology. The device has the potential of being a serious candidate for applications in sensing applications as well as in optical fiber communications. Five device process parameters and two device noise factors were identified to make the virtual device design insensitive to variation in the selected fabrication parameters. An L9 array from Taguchi method was used to optimize the device design. The simulator of ATHENA and ATLAS were used for photodiode fabrication process and electrical characterization, respectively. The results obtained for responsivity and frequency response after the optimization approach were 0.36 A/W and 21.2 GHz respectively which correspond to the optimization value for the intrinsic region length of 6 ?m, photo-absorption layer thickness of 0.505 ?m, incident optical power of 0.5 mW/cm2 and bias voltage of 3.5 V. As a conclusion, the optimum solution in achieving the desired high speed photodiode was successfully predicted using Taguchi optimization method. © (2014) Trans Tech Publications, Switzerland.